The effectiveness of exercise interventions in the improvement of sleep in older adult people: a meta-analysis - Geng, Di; Li, Xiaogang; Sun, Guotao (Frontiers in Public Health, 2025)
BackgroundSleep problems are prevalent among the older adult population, with a significant impact on their health and overall well-being. Several randomized controlled trials (RCTs) have yielded controversial results regarding the efficacy of exercise interventions in the improvement of sleep among older adult people. This systematic review and meta-analysis aim to assess the influence of exercise interventions on sleep quality within this demographic.MethodsA search was conducted across four databases, namely Web of Science, PubMed, Embase, and SportDiscus, in order to identify randomized controlled trials investigating exercise interventions and sleep in the older adult. The quality of the studies included was evaluated by two researchers according to the PEDro scale. Meta-analysis and sensitivity analysis were performed utilizing RevMan 5.4 and Stata 17 software.ResultA total of fifty studies encompassing 3,937 participants were included in the analysis. Regarding patient-reported sleep parameters, exercise interventions exhibited enhancements in sleep quality (WMD = −2.18, 95%CI: −2.83 to −1.53, p < 0.01) and reductions in insomnia severity (SMD = −0.52, 95%CI: −0.79 to −0.25, p < 0.01), albeit without significant improvements in daytime sleepiness (SMD = −0.66, 95%CI: −1.41 to 0.09, p = 0.09). In terms of clinician-reported sleep parameters, exercise interventions resulted in increased total sleep time (WMD = 8.98, 95%CI: 1.19 to 16.78, p < 0.05) and sleep efficiency (WMD = 3.66, 95%CI: 2.46 to 4.85, p < 0.01), and reduced wake time after sleep onset (WMD = −11.85, 95%CI: −15.58 to −8.11, p < 0.01), but did not decrease sleep onset latency (WMD = −3.05, 95%CI: −6.23 to 0.13, p = 0.06) or the number of awakenings during sleep (WMD = −0.73, 95%CI: −1.98 to 0.52, p = 0.25).ConclusionExercise interventions have demonstrated positive effects on enhancing sleep quality among the older adult population. This study lends support to the utilization of exercise interventions as a safe, feasible, and effective non-pharmacological treatment approach for enhancing sleep among older individuals.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024530227, Identifier CRD42024530227.